Eugène N. Marais and the Waterberg Cycad (Encephalartos eugene-maraisii Verdoorn) - Marais, Johann Lodewyk (Journal of Literary Studies, 2019)
In this article the discovery of the Waterberg cycad (Encephalartos eugene-maraisii Verdoorn) is discussed. The role that Eugène N. Marais (1871-1936) had played to introduce this plant to science, confirms the contribution of the informed “amateur” in the community. It also demonstrates that Marais had exceptional observational abilities and was able to realise the value of his observations. Furthermore, it illustrates the continuous tension between functional and scientific writing, in which case one always casts a shadow over the other (or that the reader is constantly aware of one, while he or she is engaged with the other). The so-called Marais myth had been created by both himself and other people, but the story (and oral history) of the discovery of the Waterberg cycad contributes to a rectification of the myth of Marais-the-quack/charlatan/swindler and attest to his knowledgeableness. Opsomming In hierdie artikel word die ontdekking van die Waterbergse broodboom (Encephalartos eugene-maraisii Verdoorn) bespreek. Die rol wat Eugène N. Marais (1871-1936) gespeel het om hierdie plant aan die wetenskap bekend te stel, bevestig die waarde van die ingeligte “amateur” in die gemeenskap. Dit bevestig ook dat Marais oor besondere waarnemingsvermoë beskik het en in staat was om die waarde van sy waarnemings te begryp. Terselfdertyd illustreer dit die voortdurende spanning tussen funksionele en wetenskaplike skryfwerk by Marais, sodat die een gedurig ’n skadu werp oor die ander (of dat die leser gedurig bewus is van die een, terwyl hy besig is met die ander). Die sogenaamde Marais-mite is deur sowel homself as deur ander persone geskep, maar die verhaal (of mondelinge geskiedenis) van die ontdekking van die Waterbergse broodboom dra by tot ’n regstelling van die mite van Marais-die-kwaksalwer/charlatan/boere-verneuker en getuig van sy kundigheid.